1959
DOI: 10.1103/physrevlett.3.211
|View full text |Cite
|
Sign up to set email alerts
|

Antiphase Antiferromagnetic Structure of Chromium

Abstract: triangular A^'-B", vfheny< \y2\9 orjv>0.41. The spontaneous magnetization at T = 0 is Mo=I{l+x), y>\y2\ =I(2-x){l/\y,\'l), y<\y2\,/ being here the saturation magnetization of YIG. The resulting curve (in which there is no adjustable parameter) agrees rather well with experiment (Fig. 2). These considerations can be extended to higher temperatures. The upper Curie point corresponds to ferrimagnetic order when y>y2 /^ -ot^y^y he < 1.45), and to antiferromagnetic order at higher x.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
2

Year Published

1970
1970
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 164 publications
(50 citation statements)
references
References 3 publications
3
45
0
2
Order By: Relevance
“…The main difference observed is in the temperature dependence of the resistivity, where there is a kink in the data for the nitride, characteristic of a spin-density-wave state, also observed for pure Cr [111,112]. Generally one would expect a drastic difference between a magnetic MAX phase carbide and the corresponding nitride, since in similar systems the nitride phase will typically give rise to higher transition temperatures.…”
Section: B Effect Of M a And X Elements On Magnetic Propertiesmentioning
confidence: 93%
See 4 more Smart Citations
“…The main difference observed is in the temperature dependence of the resistivity, where there is a kink in the data for the nitride, characteristic of a spin-density-wave state, also observed for pure Cr [111,112]. Generally one would expect a drastic difference between a magnetic MAX phase carbide and the corresponding nitride, since in similar systems the nitride phase will typically give rise to higher transition temperatures.…”
Section: B Effect Of M a And X Elements On Magnetic Propertiesmentioning
confidence: 93%
“…The first magnetic MAX phase showing a ferromagnetic signal was reported by Ingason et al [3], who studied the (Cr 1−x Mn x ) 2 GeC phase as epitaxial thin films on MgO [111] substrates. Ab-initio calculations were used to establish the solubility limit of Mn in Cr 2 GeC and the results indicated that the (Cr 0.75 Mn 0.25 ) 2 GeC would be stable.…”
Section: A = Gementioning
confidence: 99%
See 3 more Smart Citations